Experimental Investigation of the Effects of Process Parameters on the Radius of Curvature in Laser Forming Process of Cylindrical Surfaces - Mehdi Safari; Seyed Mohammad Miralaa; Ricardo Alves de Sousa (Metals, 2022)
In this work, the laser forming process of cylindrical surfaces is studied experimentally. For this purpose, the effects of process parameters such as laser power, laser scanning scheme, and distance between irradiation lines on the radius of curvature of the laser-formed cylindrical surfaces are examined. The design of experiment (DOE) method based on the Box–Behnken algorithm is also employed for investigations. To produce the cylindrical surfaces from flat sheets, parallel lines are used as the irradiation scheme. The results show that by increasing the laser power, the radius of curvature for a laser-formed cylindrical surface can be decreased. Additionally, the radius of curvature of the cylindrical surface increases when the scanning speed increases. In addition, it is concluded that the radius of curvature decreases when the distance between irradiation lines increases.